Określenia beneficjentów Kościoła katolickiego w szesnastowiecznej polszczyźnie - Migdał, Jolanta (Poznańskie Spotkania Językoznawcze, 2014)
The article discusses ten 16th-century designations of the beneficiaries of the Catholic Church, that is the persons endowed with offices, which were connected with specific profits. These names have been excerpted from the published volumes of Słownik polszczyzny XVI wieku (“The Dictionary of the 16th-Century Polish”). The article presents their origin and subsequent history. It is worth noting that the majority of the names of church beneficiaries that were confirmed in the 16th-century Polish language appeared just in that century. Despite the disappearance of offices and posts designated by them, the greater part of those lexemes have survived until today, if not in general Polish, than in its ecclesiastical variety as obsolete or historical lexemes.